A műfordítás mint extrémsport: Évike Tündérországban - Kappanyos, András (Studia Litteraria, 2018)
Lewis Carroll’s Alice in Wonderland has been translated into Hungarian six times. The most prominent literary personality of the six translators, Dezső Kosztolányi published his version in 1936, near the end of his life. The key hypothesis of my study is that Kosztolányi made his translation with a very specific purpose. He wanted to create the ultimate masterwork of domesticating translation: a text that cuts all its cultural connections with the source culture and replaces them with references of the target culture. He managed to create a translation of the first alice-book from which he removed every hint of englishness with the sole exception of the author’s name, and replaced them with Hungarian cultural items. This method is the exact opposite of the one Vladimir Nabokov used in his translation of Pushkin’s Eugene Onegin, which excludes any target-language references and makes up for them with bulky annotations. While nabokov’s extreme method replaces the signifiers of the original (transcoding), Kosztolányi’s replaces its signified elements and attitudes (adaptation). My paper examines his highly sophisticated tricks.